2015
DOI: 10.1103/physrevd.91.054503
|View full text |Cite
|
Sign up to set email alerts
|

In-medium modifications of open and hidden strange-charm mesons from spatial correlation functions

Abstract: We calculate spatial correlation functions of in-medium mesons consisting of strange-anti-strange, strange-anti-charm and charm-anti-charm quarks in (2+1)-flavor lattice QCD using the highly improved staggered quark action. A comparative study of the in-medium modifications of mesons with different flavor contents is performed. We observe significant in-medium modifications for the φ and Ds meson channels already at temperatures around the chiral crossover region. On the other hand, for the J/ψ and ηc meson ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 44 publications
6
59
1
Order By: Relevance
“…Note that most of these studies were performed in the quenched approximation or at rather large values of the light quark masses and so far no continuum extrapolation was performed. Results of spatial correlation functions and the corresponding spatial screening masses from lattice calculations in the charmoniun sector that include dynamical light quarks further support our findings [87,88]. Relativistic charmonium and bottomonium correlation functions computed in quenched QCD [86] have also shown that in the bottomonium channel thermal modifications set in at larger temperatures, well in the QGP phase, compared to the charmonium channel.…”
Section: Melting Temperaturessupporting
confidence: 78%
“…Note that most of these studies were performed in the quenched approximation or at rather large values of the light quark masses and so far no continuum extrapolation was performed. Results of spatial correlation functions and the corresponding spatial screening masses from lattice calculations in the charmoniun sector that include dynamical light quarks further support our findings [87,88]. Relativistic charmonium and bottomonium correlation functions computed in quenched QCD [86] have also shown that in the bottomonium channel thermal modifications set in at larger temperatures, well in the QGP phase, compared to the charmonium channel.…”
Section: Melting Temperaturessupporting
confidence: 78%
“…Thus, the value of the light quark masses are slightly larger than the physical value. This small difference , however, does not lead to any visible effects in the physical observables at zero temperature, which agree well with the experimental values [21,22]. For the valence charm and bottom quarks we use the HISQ action with the so-called ǫ-term [20], which removes the tree-level discretization effects due to the large quark mass up to O((am) 4 ).…”
Section: Lattice Setup and Details Of Analysissupporting
confidence: 61%
“…For the valence charm and bottom quarks we use the HISQ action with the so-called ǫ-term [20], which removes the tree-level discretization effects due to the large quark mass up to O((am) 4 ). The HISQ action with ǫ-term turned out to be very effective for treating the charm quark on the lattice [16,20,22,23]. The lattice spacing in our calculations has been fixed using r 1 scale defined in terms of the energy of static quark anti-quark pair V(r) as…”
Section: Lattice Setup and Details Of Analysismentioning
confidence: 99%
“…245 The horizontal solid lines denote the corresponding zero-temperature meson masses and the dashed line depicts the non-interacting theory limit of a freely propagating quark anti-quark pair. The yellow band denotes the chiral crossover temperature region, i.e.…”
Section: Spatial Correlation Functions Of Quarkoniamentioning
confidence: 99%